Respon pertumbuhan dan produksi tanaman Pakchoy (Brassica chinensis L.) akibat pemberian berbagai pupuk limbah organik - Anang Dani Alsyah; Adriani Darmawati; Sumarsono Sumarsono (Journal of Agro Complex, 2018)
The purpose of this study was to determine the effect of fertilizer application types such as wasted tea fertilizer, leaf litter fertilizer, and market wasted fertilizer on growth and yield of pakchoy mustard. The experimental design was Mono factorial Complete Randomized Design with 8 treatments and 3 replications. The treatments were without fretilization (A0), Tea Wasted fertilizer (A1), Leaf Litter fertilizer (A2), Market Wasted fertilizer (A3), Tea Wasted fertilizer + leaf litter fertilizer (A4), Tea Wasted fertilizer + Market Wasted fertilizer (A5), leaf litter fertilizer + Market Wasted fertilizer (A6), Urea fertilizer 300 kg/ha (A7). Each treatment was replicated in three times and produced 24 experimental units with experimental plots area of 1 m x 1.5 m. The observed parameters were plant height, number of leaves, leaf area index and fresh canopy production. Data were analyzed by Analysis of Variance and continuedby Duncan Multiple Range Test (DMRT) 5%. The results showed that fertilizer treatment of various types of organic waste fertilizer Tea Wasted fertilizer, Leaf Litter fertilizer, Market Wasted fertilizer, Tea Wasted fertilizer + leaf litter fertilizer, Tea Wasted fertilizer + Market Wasted fertilizer, leaf litter fertilizer + Market Wasted fertilize resulted in plant height, number of leaves, fresh leaf canopy production significantly different from treatment without fertilization and urea fertilization. The best result of fresh canopy production was found in the treatment of market waste fertilizer weighing 2,778.47 g / m², the fertilizer application of market waste fertilizer and the combination treatment of tea and market waste fertilizer yielded the best plant height with 31.16 cm, the combination treatment of waste fertilizer Tea and market produces the best leaves as much as 12.44 leaflets, and fertilizer treatment of tea waste fertilizer, market waste fertilizer, tea waste fertilizer + market waste fertilizer, and leaf litter fertilizer + market waste fertilizer yield value index of leaf area 1.23. Keywords : Organic Fertilizer, Organic Wasted Fertilizer, Pakchoy